A Case of Liver Injury after Exposure to Isopropanol: A Challenging Diagnosis - Soares Santos, Daniela (2021)
Drug-induced liver injury is hardly diagnosed, considering not only the wide range of hepatotoxic substances but also the diversity of associated phenotypes and the absence of specific biomarkers. Symptom chronology, drug or toxic exposure, and temporal association help to establish the diagnosis. Exposure to isopropanol has known but rare toxic effects. We report the clinical case of a 33-year-old female hairdresser admitted to the hospital with fatigue, epigastric pain, and jaundice. She presented the following values: aspartate aminotransferase, 485 U/L; alanine transaminase, 908 U/L; ALP, 240 U/L; GGT, 370 U/L; total bilirubin, 3.5 mg/dL; and direct bilirubin, 2.1 mg/dL. Albumin, platelet, and INR values were normal. Structural, infectious, immune, and vascular causes were excluded. Liver biopsy was suggestive of toxic hepatitis. A possible association with ibuprofen intake was considered. The patient resumed professional activity, with fatigue and jaundice relapse, as well as a new liver enzyme increase, despite ibuprofen withdrawal. It was concluded that a new hair product containing isopropanol had recently been introduced. As soon as its professional use was discontinued, there was no recurrence of the symptoms. Given the temporal association between the development of acute hepatitis and the use of an isopropanol-containing product, liver toxicity by exposure to isopropanol was assumed. This substance is metabolized in the liver and toxicity may occur by ingestion, skin exposure, or inhalation, and it is described in cases of occupational or accidental exposure. The treatment is symptomatic and comprises toxic suspension.